Drug safety perception in China: the role of media exposure and past healthcare experience: Presenter(s): Qianfeng Lu, University of Lugano, Switzerland. (April 2023) - Schulz, Peter J; Chang, Angela; Yu, Guoming; Yang, Ya
Abstract : Individuals' perception of medication safety affects their medication adherence, and through adherence their health. A person may reject a doctor's recommendation to take antibiotics if they believe antibiotics are not safe. Media and personal experiences shape individual judgments. Misleading online information may damage people's trust in drugs, see Covid-19 vaccine. The experience of adverse events can harm people's confidence in healthcare. Will unfavorable experience of healthcare in general affect drug perception? Will one effect moderate the other? We barely know that. Data from HINTS-China 2017 contains 3090 adults. Drug safety perception was indicated by drug safety status quo (The current state of drug safety is good) and drug safety amelioration (Drug safety has gradually improved in recent years) with 5-category scales from strongly disagree to strongly disagree. Media exposure was divided into traditional media (4 items) and the Internet (8 items, frequency measure, averaged); healthcare experience asks respondents satisfaction with received healthcare. We applied a multiple linear regression. We found weight-loss pills, antibiotics and vaccines were perceived the most unsafe. Besides, traditional media exposure was positively associated with drug safety status quo (? =.256**) and amelioration (? =.136**). However, Internet exposure significantly damaged people's perception of drug safety status quo (? = -.165**) and showed potential negative impact on drug safety amelioration (? = -.073). Satisfaction of healthcare services was also correlated with drug safety status quo (? =.265**) and amelioration (? =.189**) positively. Our study draws attention to how Chinese people's medicine safety perceptions are shaped by media exposure and healthcare experience. Favorable healthcare experience contributes to better medicine perception. The contrary impacts between old and new media is consistent with previous studies. This indicates drug and vaccine communications should exploit traditional communication channel and address negative perceptions on online media to promote appropriate uptake.